Pentotal anaesthetic induction time laps at the Central Operation Installation of Dr. Sardjito Central General Hospital - Ismail Sujud, Ismail Sujud (Universitas Gadjah Mada, 1987)
This investigation was done randomly at the Central Operation Installation of Dr. Sardjito Central General Hospital during the months of September, October, November and December 1986. Ninety-one patients were included who needed general anaesthesia with the degree risk of anaesthesia ASA I, ASA II and ASA III. The results showed that the mean induction time laps were as follows: I. adult patients with premedication drugs need (29.5 ÃÂ± 5.385) seconds, 2.adult patients without premedication drugs need (50.4 ÃÂ± 6.202) seconds, 3.geriatric patients with premedication drugs need (36.8 ÃÂ± 4.408) seconds, 4. geriatric patients without premedication drugs need (61.0 ÃÂ± 7.116) seconds. Key Words: anaesthetic induction time laps Ã¢â¬â premedication drugs Ã¢â¬â general anae